A comparative study on the common oral diseases among 3 to 5 year old children in a public daycare and a private preschool in Barangay Socorro, Quezon City - Austria, Dianne Angeli A.
Oral diseases remain a major public health concern especially in the Philippines where dental caries and other odontogenic infections as characterized by the presence of pulp involvement, ulceration, fistula and abscess have high incidence rate. The 2006 National Oral Health Survey shows a high incidence of dental caries and dental infections among 6 and 12 year old Filipino children. However, no epidemiological data are available for the preschoolers 3-5 years of age. This study aimed to rank and compare the most common oral findings present among 3-5 year old children in a public daycare and a private preschool in Barangay Socorro. This paper is a descriptive study using convenience sampling for the selection of the public daycare and private preschool and complete enumeration of the children who conformed to the inclusion criteria and gave consent. A total of 42 children from the Pail and Shovel Integrated School and 35 children from the Barangay Socorro Daycare Center underwent oral examination. The present or caregivers of the participants were given self-administered questionnaires regarding socio-demographic factors, oral hygiene practices, fluoride exposure and dietary habits of the children. Based on the results, dental caries (66%) is the most common oral finding among the children from both schools followed by pulp involvement (39%), fistula (13%) abscess (7.8%) and ulceration (4%). Public daycare children (7.46) exhibited a higher mean dmft value and greater prevalence of oral diseases as compared to the private preschool children (3.17).